ANALISIS PERUBAHAN VOLUME PADA CYLINDER HEAD DAN TINGGI LUBANG EXHAUST TERHADAP KENAIKAN DAYA SEPEDA MOTOR 2 LANGKAH - -, Sudarsono (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2011)
The aim of this research is to know the effect of the change of cylinder head and the height of exhaust port to obtain great and safe power. Cylinder has many ports which are used in scavenging process (proses pemasukan, pembilasan dan proses pem-buangan) Exhaust port determines compression that is occurred in two stroke engine cycle and influences the engine characters. In standard condition, revolution 1500 produced 2 Nm torque. After modification, torque decreased to 1,5Nm. New torque increased in revolution 2000 rpm with 3,1Nm. Torque reached a peak from 10,8Nm in revolution 8500rpm to 13,6Nm in revolution 10.000rpm. Power produced in standard condition was 0,4Hp in revolution 1500rpm. After modification, it decreased to 0,3Hp. New power increased in revolution 3500rpm. Power reached a peak from 12,9Hp in revolution 8500 rpm to 19Hp in revolution 10.000rpm.